2020
DOI: 10.1021/acssuschemeng.0c04679
|View full text |Cite
|
Sign up to set email alerts
|

Isosorbide and Tricyclodecanedimethanol for the Synthesis of Amorphous and High Tg Partially Biobased Copolyesters

Abstract: The synthesis and properties of amorphous poly-(tricyclodecanedimethylene-co-isosorbide terephthalate) (PTIT) with the isosorbide (IS) content ranging from 0 to 68 mol % relative to the total diol amount were investigated. Surprisingly, it was found that isosorbide enhanced the polycondensation kinetics and acted as a temporary chain linker. Polymerization kinetics improvement maximum was observed when the isosorbide content was around 9 mol %. It was also found that higher molar masses were achieved when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Besides, their molecular rigidity and chirality made them popular as platforms for developing new bio-based polymers with high glass transition temperature and/or special optical properties in the past decades. [6][7][8] Also, their non-toxicity allows them to be used in food packaging and bio-medical devices. 7,8 Particularly, the large scale production of high purity isosorbide (POLYSORB s ) by Roquette further facilitates the development of low carbon footprint polymers based on this molecule such as polyesters, polycarbonates and thermoplastic polyurethanes (TPUs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, their molecular rigidity and chirality made them popular as platforms for developing new bio-based polymers with high glass transition temperature and/or special optical properties in the past decades. [6][7][8] Also, their non-toxicity allows them to be used in food packaging and bio-medical devices. 7,8 Particularly, the large scale production of high purity isosorbide (POLYSORB s ) by Roquette further facilitates the development of low carbon footprint polymers based on this molecule such as polyesters, polycarbonates and thermoplastic polyurethanes (TPUs).…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, the properties can be readily tuned by varying the monomer type and the sequence of incorporation. 6 Succinic acid (SA) is one of the most popular short-chain aliphatic bio-based diacid, and its derivative succinyl dichloride (C4) has already shown potential for the preparation of high T g polyesters with IS or IM. 7,8 Besides, some rigid cyclic monomers, such as 2,5-furandicarboxylic acid (FDCA25) and vanillin, have also been used as bio-based cyclic building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…A second reactor was used to optimize the polycondensation step. It was a 7.5 L stainless steel batch reactor equipped with a mechanical stirrer with torque measurement, a distillation column, a vacuum line and a nitrogen gas inlet [29,30]. The reactor was charged with 10 mol of sebacic acid and 10 mol of hexanediol (~2.8 kg of final polyester).…”
Section: Esterification-polycondensation In 75 L Pilot Reactormentioning
confidence: 99%
“…[ 44–46 ] It has been reported that incorporation of ISO units into a polymer backbone leads to improvements on toughness, biodegradability, biocompatibility, and thermal stability. [ 47–50 ] Especially, isosorbide has been tried to incorporate into a variety of UPs to improve mechanical performance of the resultant UPRs. [ 51–53 ]…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] It has been reported that incorporation of ISO units into a polymer backbone leads to improvements on toughness, biodegradability, biocompatibility, and thermal stability. [47][48][49][50] Especially, isosorbide has been tried to incorporate into a variety of UPs to improve mechanical performance of the resultant UPRs. [51][52][53] Itaconic acid (IA) possesses a multifunctional structure with 𝛼,𝛽-unsaturated double bond and two carboxyl groups, thus was considered to be highly flexible for the UPR chemistry.…”
Section: Introductionmentioning
confidence: 99%